Vitalism in Man and Superman and Women in Love - Upadhyaya, Parthivendra (Rupandehi Campus Journal, 2022)
This article is an examination into the concepts of will, marriage and male-female relationship in G. B. Shaw’s Man and Superman and D. H. Lawrence’s Women in Love. The article starts will the discussion of the concept of will in both the works and moves on to discuss the works in the light of eugenics, vitalism and further analyze them under the framework of marriage and the male-female relationship. The article concludes that the two works are similar in certain aspects like being influenced by Schopenhauer’s concept of will but they still remain ways apart on other grounds like in their concept of the birth of a superman.